Numerical Evaluation of Sound Attenuation Provided by Periodic Structures - MARTINS, Mario; GODINHO, Luis; PICADO-SANTOS, Luis (Archives of Acoustics, 2013)
The use of periodic structures as noise abatement devices has already been the object of considerableresearch seeking to understand its efficiency and see to what extent they can provide a functional solu-tion in mitigating noise from different sources. The specific case of sonic crystals consisting of differentmaterials has received special attention in studying the influence of different variables on its acousticperformance.The present work seeks to contribute to a better understanding of the behavior of these structures byimplementing an approach based on the numerical method of fundamental solutions (MFS) to modelthe acoustic behavior of two-dimensional sonic crystals. The MFS formulation proposed here is used toevaluate the performance of crystals composed of circular elements, studying the effect of varying dimen-sions and spacing of the crystal elements as well as their acoustic absorption in the sound attenuationprovided by the global structure, in what concerns typical traffic noise sources, and establishing somebroad indications for the use of those structures.